Sustainability, blended learning and the undergraduate communication skills classroom: negotiating engineering undergraduates’ expectations and perceptions - Sivapalan, S. (Emerald Group Publishing Ltd., 2017)
Purpose: This paper aims to discuss the outcomes of a study conducted to explore the perceptions and expectations of undergraduate engineering learners on the potential of incorporating sustainability within the Professional Communication Skills (PCS) module, via blended learning. Design/methodology/approach: A mixed methods case study approach was used, using surveys, learner reflections and interviews. Findings: Key findings include (a) learners finding a heightened sense of awareness of environmental, social and cultural dimensions of sustainability, (b) development of sustainability literacy and communication skills for the real world, (c) scepticism and apprehension of blended learning teaching and learning methods, (d) development of capacity for self-directed learning resulting from flipped learning and (e) differences in quality of peer and lecturer interaction online and in the traditional classroom set up. Originality/value: Sivapalan’s (2015) study suggests that Malaysian engineering graduates lack sustainability knowledge, competences and values, and often struggle to cope with professional responsibilities that require them to exercise these literacies. Much of this is attributed to the lack of sustainability integration within the undergraduate engineering curriculum, and within teaching approaches used. To date, there is little research within the Malaysian engineering education context to gauge the extent to which non-technical academic modules such as the PCS module could be used as a platform to incorporate sustainability learning outcomes. Research to gauge learners’ feedback and reflections on the integration of sustainability via non-technical modules and blended learning approaches is also scarce. © 2017, © Emerald Publishing Limited.